Association between social determinants of health and direct economic burden on middle-aged and elderly individuals living with diabetes in China - Guo, Jianwei; Wu, Yun; Deng, Xinlei; Liu, Zifeng; Chen, Lijin; Huang, Yixiang (PloS one, 2021)
The aim of this study was to determine the association between social determinants of health and direct economic burden on Chinese middle-aged and elderly individuals living with diabetes in China. This study used data from the baseline wave of The China Health and Retirement Longitudinal Study (CHARLS) database, covering 17,708 middle-aged and elderly residents in China. The population with diabetes was grouped into those diagnosed with diabetes mellitus (DDM) and those undiagnosed with diabetes mellitus (UDM). Direct economic cost data, including total direct medical costs (TC) and out-of-pocket (OOP) payments, were extracted as outcome variables. A two-part model was applied to analyze the association between social determinants of health and direct economic burden. In our analysis, we included 958 patients with DDM and 1,285 patients with UDM. The mean TC and OOP payments were 11,193 CNY (US $1,733; 6.46 CNY = 1 USD) and 7,266 CNY (US $1,125) in DDM patients, and 3,700 CNY (US $573) and 3,060 CNY (US $474) in UDM patients. Rural-urban status (p<0.05), regional status (p<0.05), household personal consumption expenditures (p<0.05), and comorbidities(p<0.05) were crucial factors associated with medical costs in people with diabetes. Although progress has been made in the development of current health policies intended to contain the direct economic burden of diabetes, the gaps in that burden in populations with different social characteristics remains a burning issue. More policy breakthroughs are needed to achieve health equity.